TETANUS IN A BUCK AND ITS EFFECTIVE TREATMENT: A CASE REPORT - Selvam, A; Veerapandian; Sekar, M; Venkataraman, K S; Suresh, R V; Krishna, Mahesh (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
A four-month-old buck was presented to the large animal clinic, out patient medical unit, Madras Veterinary College Teaching Hospital with symptoms of erect ears and rigid limbs. The buck was tentatively diagnosed as tetanus based on clinical signs and then confirmed by staining techniques. Though prognosis is grave for tetanus, the case was successfully treated with tetanus anti-toxin, antibiotics and electrolytes and the buck became normal.
Keywords: Tetanus; Buck; Diagnosis and Tetanus anti-toxin